Double Fano Resonances in S-Shaped Plasmonic Metasurfaces in Terahertz Region - Xu, Weihang; Chen, Lingling; Zhu, Fangming; Liu, Jianjun; Sui, Chuanshuai; Hong, Zhi (Frontiers in Physics, 2020)
We numerically and experimentally demonstrated double Fano resonances in a simple S-shaped plasmonic metasurface in the terahertz frequency range. Apart from the electric-LC resonance and electric dipole (ED) resonance, two trapped modes are excited in two different types of asymmetric S-shaped structures in the frequency range 0.2–1.4 THz, which are mainly attributed to a magnetic dipole (MD) and an electric quadrupole (EQ). Thereafter, double Fano resonances [one Fano and one electromagnetically induced transparency (EIT) resonance] are achieved via the coupling of the two dark trapped modes and a broad bright ED at normal incidence of the metasurfaces. Furthermore, under oblique incidence, strong Fano responses can be observed; they are considerably enhanced in asymmetric structures, and even in a symmetric structure. The proposed S-shaped plasmonic metasurfaces are easy to fabricate and have potential applications in multi-wavelength optical switches, filters, and sensors.